2006
DOI: 10.1111/j.1365-2036.2006.03012.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble CD163 correlate with the inflammatory process in coeliac disease

Abstract: Summary Backgound In coeliac disease, following the introduction of a gluten‐free diet, monitoring mucosal disease activity requires repeated small intestinal biopsies. If a test measuring a circulating inflammatory marker was available, this would be clinically valuable. Aim To determine if levels of soluble CD163, a scavenger receptor shed by tissue macrophages, correlated with the inflammatory lesion in coeliac disease. Methods Serum samples were collected from 131 patients with untreated coeliac disease, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Bec ause the EMA and anti-tTG responses may remain elevated in CD on a GFD, it may be useful to measure soluble CD163, a sc avenger rec eptor shed by tissue macrophages and correlated with the inflammatory lesion in CD. Those subjec ts with a more severe (Marsh grade 3) lesion had higher levels of CD163 than did those with a milder (Marsh grade 2, grade 1 or grade 0) lesion [53] . Further studies are needed.…”
Section: Serologymentioning
confidence: 91%
“…Bec ause the EMA and anti-tTG responses may remain elevated in CD on a GFD, it may be useful to measure soluble CD163, a sc avenger rec eptor shed by tissue macrophages and correlated with the inflammatory lesion in CD. Those subjec ts with a more severe (Marsh grade 3) lesion had higher levels of CD163 than did those with a milder (Marsh grade 2, grade 1 or grade 0) lesion [53] . Further studies are needed.…”
Section: Serologymentioning
confidence: 91%
“…Whether CD163-depndent clearance of TWEAK could be responsible for diminished amounts of TWEAK in PBMC cell cultures needs to be determined. Elevated expression of CD163 has been reported in chronic diseases such as atherosclerosis, asthma, and celiac disease [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…A soluble form of CD163 (sCD163) present in serum (Sulahian et al 2001;Moller et al 2002b) was some years ago identified and shown to be a marker of macrophage activity. Recent clinical studies have further revealed that sCD163 is a promising marker-molecule for macrophage activation in diseases such as hemophagocytic syndrome, sepsis, autoimmune disorders, and liver disease (Baeten et al 2004;Schaer et al 2005;Moller et al 2007Moller et al , 2006Daly et al 2006;Hiraoka et al 2005).…”
Section: Introductionmentioning
confidence: 99%